9 Stat. at Large of Pa. 347, ch. 836, § 4 (1903) - (:unkn) unknown (My University, 1779)
Prohibited firearm possession for people "disaffected to the liberty and independence" of the state, empowered officers to disarm any person who did not take an oath."
Keywords: LOYALTY OATH REQUIRED; POSSESSION - DANGEROUS PERSONS